O processo de trabalho no núcleo ampliado de saúde da família e atenção básica - Sá, Joseires Gleydson Santos Benicio de (2020)
The Center for Extended Family Health and Primary Care - NASF-AB, appears in the Unified Health System with the proposal to expand the scope of Brazilian Primary Care actions, through a logic that follows the precepts of interprofessionality. Thus, this article aims to analyze the work process of NASF-AB in a capital of northeastern Brazil in this work reality. An exploratory and descriptive research with a qualitative approach was carried out, with four health district directors and nine NASF-AB workers. Data were collected through in-depth interviews and submitted to content analysis. The results suggest two categories: The role of NASF-AB; and NASF-AB's doing. It was concluded that the participants understand that the work in Primary Care as a whole, must be guided by interprofessionality, and that the NASFAB is important for health promotion, so that it is essential to maintain them to ensure a promotion effective and quality health care for the population.